2018
DOI: 10.1186/s12889-018-5720-2
|View full text |Cite
|
Sign up to set email alerts
|

School and classroom effects on Daily Physical Activity (DPA) policy implementation fidelity in Ontario classrooms: a multi-level analysis

Abstract: BackgroundThis paper examines school and classroom effects on Daily Physical Activity (DPA) policy implementation in classrooms in Ontario, Canada. In 2005 the Ontario Ministry of Education mandated a policy requiring school boards to “ensure that all elementary students, including students with special needs, have a minimum of twenty minutes of sustained MVPA each school day during instructional time”. Based on an adaptation of Chaudoir’s conceptual framework, this paper contributes to understanding the exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
2
1
Order By: Relevance
“…Recent work has highlighted the importance of self-efficacy—similar to competence—in explaining teachers’ CPA implementation [ 29 ]. The current work did not find that perceived competence significantly explained implementation, despite the robust body of evidence showing the importance of teacher self-efficacy when implementing innovations in their classrooms [ 22 , 24 , 28 ]. However, our results showing the importance of autonomy, a motivational component articulated in Self Determination Theory, are relatively novel.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Recent work has highlighted the importance of self-efficacy—similar to competence—in explaining teachers’ CPA implementation [ 29 ]. The current work did not find that perceived competence significantly explained implementation, despite the robust body of evidence showing the importance of teacher self-efficacy when implementing innovations in their classrooms [ 22 , 24 , 28 ]. However, our results showing the importance of autonomy, a motivational component articulated in Self Determination Theory, are relatively novel.…”
Section: Discussioncontrasting
confidence: 78%
“…Organizational leadership is an important determinant of the implementation of many evidence-based practices [ 17 , 18 ], including CPA [ 19 , 20 , 21 ]. The availability of resources, perceived benefits of CPA, and perceived implementation climate have all been associated with teachers’ CPA implementation [ 22 , 23 , 24 ]. Determinants of behavior change include individual-level characteristics such as knowledge, attitudes, and self-efficacy [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent evaluation found that only 23% of Ontario teachers were meeting this expectation [23], which is a significant drop from 50% in 2015 [24,25]. Several studies have investigated barriers to DPA implementation and identified lack of access to DPA resources and inadequate teacher training as important barriers to DPA implementation [24][25][26][27][28][29][30][31][32]. These barriers are noteworthy to empirically address as they can be targeted most directly and efficiently compared to the more systemic barriers such as school culture, implementation climate, and leadership support, given the extensive resourcing available, albeit across disparate sources, which require minimal teacher training to effectively implement [1].…”
Section: Introductionmentioning
confidence: 97%
“…Teachers have been documented as using a variety of resources to implement DPA, including videobased activities (e.g., GoNoodle or YouTube dance), playing active games like Simon Says, and incorporating physical activity directly into learning activities (2 × 5 = 10 jumping jacks) [9,10,12]. However, a recent evaluation found that only 23% of Ontario teachers were meeting this expectation [23], which is a significant drop from 50% in 2015 [24,25]. Several studies have investigated barriers to DPA implementation and identified lack of access to DPA resources and inadequate teacher training as important barriers to DPA implementation [24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%